2019
DOI: 10.31234/osf.io/yma3s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing speech rhythm using spectral coherence between jaw displacement and speech temporal envelope

Abstract: Lower modulation rates in the temporal envelope (ENV) constitute the rhythmic frames in speech and are crucial for speech comprehension in terms of neuronal entrainments at δ- and θ-rates. The jaw plays the role of a carrier articulator producing the low-frequency modulations in this process. This paper introduces a method to examine the joint roles of jaw oscillation and ENV in formulating rhythmic frames using spectral coherence. Relative powers in the frequency bands corresponding to the δ- and θ-oscillatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To integrate both temporal modulation and the opening and closing cycles of the mouth for the characterization of the rhythmic frame, spectral coherence has been used. 77,78 The coherence is calculated from the spectra of two signals to show the connectivity between them in terms of their correlation in the frequency domain. It combines interrelated signals into one system.…”
Section: 76mentioning
confidence: 99%
See 1 more Smart Citation
“…To integrate both temporal modulation and the opening and closing cycles of the mouth for the characterization of the rhythmic frame, spectral coherence has been used. 77,78 The coherence is calculated from the spectra of two signals to show the connectivity between them in terms of their correlation in the frequency domain. It combines interrelated signals into one system.…”
Section: 76mentioning
confidence: 99%
“…[63][64][65][66]77 It has further been demonstrated that in the coherence, the frequency density in the lower range (0.5-3 Hz) and higher range (3)(4)(5)(6)(7)(8)(9) are different between longer and shorter utterances. 78 Spectral coherences have also been calculated between the surface electromyographic signals at the lips and the jaw and the temporal envelopes; they were also effective to outline the rhythmic structure in speech. 79…”
Section: 76mentioning
confidence: 99%